Kynurenine pathway is altered in patients with SLE and associated with severe fatigue. Issue 1 (23rd May 2018) - Åkesson, Karolina; Pettersson, Susanne; Ståhl, Sara; Surowiec, Izabella; Hedenström, Mattias; Eketjäll, Susanna; Trygg, Johan; Jakobsson, Per-Johan; Gunnarsson, Iva; Svenungsson, Elisabet; Idborg, Helena
Abstract : Objective: Fatigue has been reported as the most disturbing symptom in a majority of patients with SLE. Depression is common and often severe. Together these symptoms cause significant morbidity and affect patients with otherwise relatively mild disease. Tryptophan and its metabolites in the kynurenine pathway are known to be important in several psychiatric conditions, for example, depression, which are often also associated with fatigue. We therefore investigated the kynurenine pathway in patients with SLE and controls. Methods: In a cross-sectional design plasma samples from 132 well-characterised patients with SLE and 30 age-matched and gender-matched population-based controls were analysed by liquid chromatography tandem mass spectrometry to measure the levels of tryptophan and its metabolites kynurenine and quinolinic acid. Fatigue was measured with Fatigue Severity Scale and depression with Hospital Anxiety and Depression Scale. SLE disease activity was assessed with Systemic Lupus Erythematosus Disease Activity Index (SLEDAI). Results: The kynurenine/tryptophan ratio, as a measure of indoleamine 2, 3-dioxygenase (IDO) activity, was increased in patients with SLE. Patients with active disease (SLEDAI ≥6) showed lower tryptophan levels compared with controls (54 µM, SD=19 vs 62 µM, SD=14, p=0.03), although patients with SLE overall did not differ compared with controls. Patients with SLE had higher levels of tryptophan metabolites kynurenine (966 nM, SD=530) and quinolinic acid (546 nM, SD=480) compared with controls (kynurenine: 712 nM, SD=230, p=0.0001; quinolinic acid: 380 nM, SD=150, p=0.001). Kynurenine, quinolinic acid and the kynurenine/tryptophan ratio correlated weakly with severe fatigue ( rs =0.34, rs =0.28 and rs =0.24,  respectively) but not with depression. Conclusions: Metabolites in the kynurenine pathway are altered in patients with SLE compared with controls. Interestingly, fatigue correlated weakly with measures of enhanced tryptophan metabolism, while depression did not. Drugs targeting enzymes in the kynurenine pathway, for example, IDO inhibitors or niacin (B12) supplementation, which suppresses IDO activity, merit further investigation as treatments in SLE.